Characteristics of Progesterone Synthesis In Isolated Luteal Cells - Tan, Cheong Huat (1982)
Single cells were prepared from the luteinized rat ovary, and the characteristics of progesterone synthesis by these cells were examined. The isolated luteal cells were viable and functional, and respond to luteinizing hormone (LH) stimulation by synthesizing progesterone in vitro. In the absence of exogenous glucose, the rate of progesterone synthesis was 0.23 ng/ml/min. LH increased this rate 2-fold, and the duration of the initial linear phase of this reaction was sustained for up to 60 min, compared to the controls which were linear for only 15 min. This effect was dose-related: maximal stimulation was achieved with 1 J1g LH/ml, while a minimal but significant stimulation was elicited with 61 pg/ml. This steroidogenic activity was also increased by the addition of exogenous glucose and bovine serum albumin. These data serve to establish the optimum conditions for the use of single cells in studies pertaining to mechanism of LH action.